Fuel Saving Model on Seine Net Boats in Palabuhanratu - Dwi Putra Yuwandana; Mohammad Fachrurezky Pahlevi; Vita Rumanti Kurniawati; Yopi Novita; Eko Sri Wiyono (International Journal of Marine Engineering Innovation and Research, 2025)
Fuel oil is a critical input for seine net fishing in Palabuhanratu, yet its rising cost imposes a heavy burden on fishers and boat owners. Although fishers intuitively adjust engine power to reduce fuel use, the effectiveness of these practices remains unclear due to limited data. This study examines fuel consumption patterns of seine net boats and explores potential savings strategies. Data were collected on daily fuel use, vessel speed, trip duration, and operating distances across boats with engines of different ages. Results show that fishing trips follow eight distinct phases: preparation, outbound steaming, setting, hauling, fish hunting, resting, inbound steaming, and berthing. The highest fuel use occurs during fish hunting as well as outbound and inbound steaming, where high speeds and long durations dominate. Engine age strongly influences efficiency: a 6-month-old engine achieved a specific fuel consumption (SFC) of 328.42 g/kWh, compared to 499.33 g/kWh for a 7-year-old and 873.41 g/kWh for a 12-year-old engine. Simulation of reduced speeds during fuel-intensive phases suggests potential savings of 1.7%–21.7%, without compromising operational feasibility. These findings highlight the importance of managing vessel speed and engine condition to optimize fuel efficiency in seine net fisheries.